Getting children writing story ideas for children aged 3-11 - Brownhill, Simon (Los Angeles SAGE, 2013)
"This book is a practical guide designed to stimulate story-writing in the early years and primary classroom. It offers a collection of novel and effective ideas which can be used by educators to energize, excite and motivate children to willingly write stories across the 3-11 age phase."--page [4] of cover.
1. Pen to paper stories -- 2. Design and make stories -- 3. Being stories -- 4. Craft stories -- 5. Engaging stories -- 6. Technology stories -- 7. Location stories -- 8. Boys stories -- 9. Creative stories -- 10. Random stories -- Appendices.
Includes bibliographical references (pages [243]-281) and index.
Keywords: English language -- Composition and exercises -- Study and teaching (Elementary)